UTANG DARI PINJAMAN ONLINE SEBAGAI DASAR PERMOHONAN PAILIT DALAM PERSPEKTIF HUKUM KEPAILITAN - Hidayat, Irfan (Fakultas Hukum Universitas Narotama, 2026)
The rapid development of financial technology (fintech) has significantly transformed financial transaction mechanisms, particularly through the emergence of peer-to-peer (P2P) lending-based online loan services that have become increasingly popular among the public. These platforms facilitate lending and borrowing activities directly between individuals or institutions without the intermediation of traditional financial institutions. However, along with this innovation, new legal challenges arise, especially regarding the status of debts originating from online loans and their potential to serve as the basis for bankruptcy petitions. Under Law No. 37 of 2004 on Bankruptcy and Suspension of Debt Payment Obligations (PKPU), the definition of debt is broad, encompassing all monetary obligations, both present and future, as long as they are collectible and enforceable by the creditor. Therefore, debts arising from online loan agreements that satisfy the legal conditions of contracts as stipulated in Article 1320 of the Indonesian Civil Code—which include mutual consent, capacity, a certain subject matter, and a lawful cause—can be categorized as valid debts within the framework of bankruptcy law. This study adopts a normative juridical research method utilizing both statutory and conceptual approaches. Through this method, the research aims to analyze the legal construction of online loan debts in relation to bankruptcy law, evaluate the extent of legal protection for creditors and debtors, and provide a clearer understanding of how fintech-based debt relationships fit within Indonesia’s existing legal system. Keywords: Online Loan, Bankruptcy Petition, Bankruptcy Law.